THE BASIC PRINCIPLES OF CREATING A SIMPLIFIED ELECTRONIC SIMULATORS ARTILLERY SYSTEMS - Dmytry Chopа; Anatoliy Y. Derevjanchuk; Denys R. Moskalenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article deals with the principle of creating an electronic simulator direct fire towed artillery systems. The ways to improve the safety of soldiers in combat firing by quality and quick training of personnel, using computer simulations. It provides the basic features and capabilities of computer simulator developed direct fire, and the expediency of the use of simulators in the training of gunners and commanders gun on practical training. A general structural diagram of an electronic simulator direct fire on the basis of the D-30 howitzers. Shows the advantages of using electronic simulators during the complex military-political situation, which requires the preparation of high-quality professionals in a short time, and the lack of a sufficient number of hours for practical classes.